IMF Committee on Balance of Payments Statistics : Annual Report 2013. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2014)
The 2013 Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) provides an overview of recent trends and discrepancies in global balance of payments statistics, and summarizes the Committee's work program during 2013 andthe issues the Committee plans to address in the coming year.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet